Crustal anatexis in the Aouli-Mibladen granitic complex: A window into the middle crust below the Moroccan Eastern Variscan Meseta. (June 2019) - Elabouyi, Mustapha; Dahire, Mohamed; Driouch, Youssef; Duchêne, Stéphanie; Kriegsman, Leo M.; Ntarmouchant, Ahmed; Kahou, Zia Steven; Severac, Jean Luc; Belkasmi, Mohammed; Debat, Pierre
Abstract: The Moroccan Variscan belt comprises numerous granitoid bodies, which have been isotopically studied, but still lack a detailed petrogenetic model. The Variscan Aouli-Mibladen granitic complex in the Moroccan Eastern Meseta provides an excellent opportunity for studying the petrogenesis and the relationship with adjacent Cambro-Ordovician metasediments. This region exposes mainly M-to I-type metaluminous mafic to granitic bodies as well as migmatites and peraluminous S-type anatectic granites. An exceptional xenoliths and garnets cumulate deposit covers an area of ∼2 km 2 located NE of the complex. The S-type suite includes cordierite bearing microgranite dykes and two small two-mica leucogranitic stocks, crosscutting the eastern metamorphic aureole of the complex. Petrological analysis shows that biotite dehydration melting reactions produced anatectic melt and peritectic cordierite and garnet. Garnet shows complex zoning profiles, with typical prograde growth zoning in the core, and resorption and reprecipitation rims. Peritectic cordierite ( X Fe = 0.37) is associated with restitic biotite ( X Fe = 0.65), whereas abundant cotectic cordierite ( X Fe = 0.65) belongs to the granites paragenesis (Bt + Kfs + Pl + Crd + Qtz). Garnet crystals are also frequently mantled by a retrograde cordierite type. Thermodynamic modelling shows that biotite dehydration melting took place under granulitic facies conditions (830–870 °C and 6 kbar), producing a significant amount of peraluminous melts. Their ascent and emplacement led to the S-type suite of the Aouli-Mibladen complex, including the local xenolith-cumulate deposit. We envisage a petrogenetic model during the Variscan orogeny, in which mantle derived mafic magmas stagnated in large reservoirs at 18–20 km depth, causing isobaric heating and partial melting of the surrounding metapelitic protolith. Differentiated M-I-type and S-type magmas were emplaced at higher levels concomitantly, with limited mixing and mingling during their final crystallization, at a depth of 9–10 km leading to contact metamorphism (600 °C, 3 kbar). These findings open a window into the hitherto unknown Moroccan Variscan mid-crust and permit to discuss the nature and age of the underlying basement terranes. Highlights: Direct observation of mantle-crust interaction during the Variscan Orogeny, Morocco. Partial melting of pelitic protholith, formation of anatexites. Pseudosection modelling, cordierite and garnet as key peritectic minerals. Thermal state of Variscan Moroccan middle and upper crust. Petrogenetic model for the Variscan belt, key for geodynamic considerations.